การผลิตเฟอร์ฟูรัลจากแกลบโดยไฮโดรไลซิสควบคู่กับการสกัดด้วยคาร์บอนไดออกไซด์ภาวะเหนือวิกฤต - วิรังรอง แสงอรุณเลิศ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
Furfural is produced by acid catalytic dehydration of pentose, which is obtained by acid catalytic hydrolysis of pentosan from biomass. Furfural that produced in a reactor disappears by side reactions such as polymerization and decomposition. The aim of this research was to study the furfural production from rice husk by hydrolysis accompanying supercritical CO[subscript 2] extraction. This study was conducted in an 80-ml high pressure and high temperature semi-batch reactor. The two-level factorial experimental design method was used to optimize the production with respect to furfural yield. The process variables are temperature range of 70-130 degree celsius, pressure 90-160 bar, sulfuric acid concentration 1 to 5 (%wt) and ratio of liquid to solid 5:1 to 15:1 (vol./wt.). The optimum condition was at temperature of 130 degree celsius, pressure 160 bar, sulfuric acid concentration 5 %wt, liquid : solid ratio of 5:1 and CO[subscript 2] flow rates of 5 g/min which gave 17.71% of theoretical furfural yield. The results obtained from the experimental design showed that the furfural yield increased with increasing temperature, pressure and sulfuric acid concentration while decreasing ratio of liquid to solid could improved furfural yield. Because of furfural yield rather low, further experhments were conducted by increasing CO[subscript 2] flow rates and the furfural production was performed in two-stage process (pre-hydrolysis and dehydration). The condition for maximum yield was at temperature of 160ํC, pressure of 180 bar, sulfuric acid concentration of 7 %wt, liquid : solid ratio of 1:1, CO[subscript 2] flow rates of 10 g/min and pre-hydrolysis time of 15 minutes which gave 80.14 % of theoretical furfural yield.